أثر العجز في المعاملات المالية المعاصرة - حمي, وليد; درقيش, محمد عبد الجليل; زواري احمد, بوبكر (University of Eloued-جامعة الوادي, 2022)
"الحمد لله حتى يبلغ الحمد منتهاه و الصلاة والسلام على من لا رسول بعده محمد صلى الله عليه وسلم. نتناول في البحث دارسة موضوع العجز وأثره على المعاملات المالية المعاصرة وقد قسمناه إلى مبحثين و خاتمة . المبحث والأول: حقيقة العجز وأسباب وأنواعه و قسمناه إلى مطلبين ذكرنا في المطلب الأول المفهوم اللغوي للعجز وكذلك الاصطلاحي ، وعالج المطلب الثاني الأسباب المؤدية إلى هدا العجز كما تطرقنا إلى أنواعه كالعجز باعتبار فقد القدرة سواء القدرة البدنية كالمريض ، أو سبب فقد الأهلية كالمجنون . أما المبحث الثاني: تطرقنا إلى أثر العجز في المعاملات المالية المعاصرة وقد جعلناه في أربع مطالب، ففي المطلب الأول تطرقنا إلى مفهوم البطاقات البنكية وصورها وحكمها والشرعي وبينا فيه أثر العجز ، أما المطلب الثاني فكان فيه أثر العجز في الودائع المصرفية فتطرقنا إلى مفهوم مما وكذلك صورها وحكمها وأثر العجز فيها، والمطلب الثالث تناولنا قيه أثر العجز في بيع التقسيط وتطرقنا فيه مفهومه وحكمه وبعض صوره وأثر العجز فيه أما المطلب الرابع درسنا أثر العجز في السندات و تناولنا فيه مفهوم السندات و أحكام التعامل بها وأثر العجز فيها. ""Praise be to God until praise reaches its limit, and prayers and peace be upon the one after whom there is no messenger, Muhammad, may God’s prayers and peace be upon him. In the research, we study the issue of deficit and its impact on contemporary financial transactions, and we have divided it into two sections and a conclusion. The first topic: the reality of disability, its causes and its types, and we divided it into two demands. In the first requirement, we mentioned the linguistic concept of disability as well as the idiomatic one. The second requirement dealt with the causes leading to this disability, as we touched on its types such as disability, considering the loss of ability, whether physical capacity is like a patient, or the cause of losing capacity like an insane person. As for the second topic: we touched on the impact of the deficit in contemporary financial transactions, and we made it into four demands. Its ruling and the effect of deficit in it, and the third requirement we dealt with the effect of deficit in installment sale and we touched on its concept and wisdom and some of its images and the effect of deficit in it"
مذكرة ماستر
Keywords: العجز - المعاملات المالية المعاصرة - البطاقات البنكية - الودائع المصرفية; Deficit - contemporary financial transactions - bank cards - bank deposits